Long term average speech spectra of Turkish - YÜKSEL, MUSTAFA (TAYLOR & FRANCIS LTD, 2018)
Long-term average speech spectra (LTASS) are a voice analysis method that is recommended to be used in various areas, such as hearing aid fittings, automatic speaker recognition and voice disorders. Evaluations of LTASS in different languages have been published; however, this analysis has not been conducted for the Turkish. Therefore, the first aim of this study was to conduct this analysis, generate normative values and compare the obtained LTASS curve for the Turkish with those obtained for other languages reported in the literature. To achieve this objective, 40 adults with healthy hearing and speech characteristics were evaluated. Long-term spectral shape is presented in a graphical form, with visual comparisons to other research findings. Spectral differences by gender were analyzed, with statistically significant differences observed between gender groups and overall LTASS. The LTASS curve for the Turkish is similar to those reported for other languages, but there are also observable differences. Use of generated speech signals in hearing aid fitting procedures is recommended.
Keywords: Acoustic analysis; long-term average spectra; normal voice; Turkish; voice analysis; VOICE QUALITY; HEARING; IDENTIFICATION; RECOGNITION; SPEAKING